Ethics after theory - Kok Hui, CHAN; Jeffrey, Jeffrey (Institut Teknologi Sepuluh Nopember, 2017)
Today, architectural theory has atrophied. Despite a perceived need for different theoretical ways of clarifying, explaining and understanding the complex phenomena of contemporary architectural production prior to a designer’s intervention, there are few existing theoretical frameworks. Without either the descriptive or projective enablement by theory, conscientious and critical practices in architecture will have few alternatives against the tide of neoliberal city-making. In this paper, I make a pun of Speaks’s (2006) paper titled, ‘Intelligence after theory’ by arguing that while (design) intelligence is necessary, it is however not sufficient. Ethics is also needed in architecture. Through a brief restatement of a canonical debate in the critical school of architectural theory, I argue why ethics is needed in architecture, and how ethics could be further developed through theory and theorization.